2018
DOI: 10.3758/s13415-018-00680-1
|View full text |Cite
|
Sign up to set email alerts
|

Differential impact of ventromedial prefrontal cortex damage on “hot” and “cold” decisions under risk

Abstract: The ventromedial prefrontal cortex (vmPFC) is known to play a key role in reward processing and decision making. However, its relative contribution to affect-rich (Bhot^) and affect-poor (Bcold^) decisions is not fully understood. Damage to vmPFC is associated with impaired performance on laboratory tasks of decision making under ambiguity and risk. In the current study, we tested the hypothesis that vmPFC is critical for adaptive risk taking under Bhot^conditions specifically. Participants included patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…For example, adolescents took more risk than adults in the hot but not in the cold CCT (Figner et al, ). A similar pattern was observed for patients with ventromedial prefrontal cortex (VMPFC) lesions compared to healthy controls (Spaniol, di Muro, & Ciaramelli, ). Biological dissociations have also been reported: electrodermal activity (EDA) only increased from baseline to decision phase in the hot and not the cold version of the task (Figner et al, ).…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…For example, adolescents took more risk than adults in the hot but not in the cold CCT (Figner et al, ). A similar pattern was observed for patients with ventromedial prefrontal cortex (VMPFC) lesions compared to healthy controls (Spaniol, di Muro, & Ciaramelli, ). Biological dissociations have also been reported: electrodermal activity (EDA) only increased from baseline to decision phase in the hot and not the cold version of the task (Figner et al, ).…”
Section: Introductionsupporting
confidence: 67%
“…Distinctive patterns of information use have, for example, been observed in adolescents (Figner et al, ) and older adults (Huang, Wood, Berger, & Hanoch, ): both were shown to take less information into account than young and middle‐aged adults when making decisions in the hot and warm CCT, respectively. Aberrant sensitivity to information has also been observed in several patient groups: compared to healthy controls, crack cocaine users (Kluwe‐Schiavon, Viola, Sanvicente‐Vieira, Pezzi, & Grassi‐Oliveira, ), heroin‐dependent persons (Saleme et al, ), and individuals with lesions in the VMPFC (Spaniol et al, ) paid less attention to probabilities. Decreased information sensitivity has also been reported in healthy individuals.…”
Section: Introductionmentioning
confidence: 98%
“…In patient studies, more erratic judgments and greater inconsistencies in choice selections under conditions of uncertainty (e.g., risky or ambiguous decisions) have been observed for patients with focal damage to the vMPFC compared to age-and education-matched controls (Henri-Bhargava, Simioni, & Fellows, 2012;Fellows, 2011;Fellows & Farah, 2007). In fact, additional research has shown that the vMPFC may even be more specifically involved in value-based decision-making for risky choices across both human and animal models (Spaniol et al, 2019;Abela & Chudasama, 2013;Weber & Huettel, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…A more recent study with vMPFC patients showed increased risk-taking only under "hot" decision-making conditions in which immediate reward feedback was provided after each choice, requiring the online integration of affective states with other sources of information (e.g., reward probability or magnitude), and not under "cold" conditions where feedback was provided cumulatively at the end of the task, thus minimizing integration demands and leading to more deliberate decision-making (Spaniol, Di Muro, & Ciaramelli, 2019). Probability discounting tasks like the one used in this study represent cold conditions, as no feedback is provided, and, because they are quite different from card tasks like the one used by Spaniol et al, they provide a test of the robustness of their findings.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies put it as a part of the default network (Christoff et al, 2016) but it is closely linked with the mind, intellect and memory. Damages to this region has shown reduced risk aversion (Spaniol et al, 2019). We further hypothesize that increased connectivity between the ego and default subsystems could be linked to narcissistic personality traits.…”
Section: Egomentioning
confidence: 79%